2013
DOI: 10.2147/cia.s47462
|View full text |Cite
|
Sign up to set email alerts
|

Age-related reduction of cerebral ischemic preconditioning: myth or reality?

Abstract: Stroke is one of the leading causes of death in industrialized countries for people older than 65 years of age. The reasons are still unclear. A reduction of endogenous mechanisms against ischemic insults has been proposed to explain this phenomenon. The “cerebral” ischemic preconditioning mechanism is characterized by a brief episode of ischemia that renders the brain more resistant against subsequent longer ischemic events. This ischemic tolerance has been shown in numerous experimental models of cerebral is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…The other strategy is neuroprotection targeting various components of the cascade during ischemic insult, which is supported by preclinical data for many agents (Fisher, 2011; Dirnagl and Endres, 2014; Fisher and Saver, 2015). Unfortunately, all prior drug development of neuroprotective agents has been unsuccessful, no neuroprotective drug demonstrated unequivocal efficacy in clinical trials (Fisher, 2006; Hossmann, 2006; Della-Morte et al, 2013).…”
Section: Translational Potential Of Ginseng and Ginsenosides In Strokmentioning
confidence: 99%
“…The other strategy is neuroprotection targeting various components of the cascade during ischemic insult, which is supported by preclinical data for many agents (Fisher, 2011; Dirnagl and Endres, 2014; Fisher and Saver, 2015). Unfortunately, all prior drug development of neuroprotective agents has been unsuccessful, no neuroprotective drug demonstrated unequivocal efficacy in clinical trials (Fisher, 2006; Hossmann, 2006; Della-Morte et al, 2013).…”
Section: Translational Potential Of Ginseng and Ginsenosides In Strokmentioning
confidence: 99%
“…Aging leads to loss of viability, an increase in vulnerability, and a progressive decrease in the endogenous mechanisms of defense. IPC is one of the most important endogenous protective mechanism against ischemia, but it decreases with aging [98]. An in-vivo study using young and aged rats (4 and 24 months) subjected to IPC (3-min ischemia) followed by 10-min ischemia, through the assessments of histology and the immunoreactivity of N-methyl-D-aspartic acid receptor 1 and caspase-3 active peptide in the hippocampal CA1 region performed 8 days after full ischemia, clearly demonstrated that the degree of cerebral protection against ischemia was reduced in the aged and preconditioned rats compared with the young rat [99].…”
Section: Age-related Differences Of Pkcs In Brainmentioning
confidence: 99%
“…Mechanisms to explain the age-related reduction of cerebral IPC may be multiple and include the physiological reduction in neurons, mitochondrial dysfunction, increase in oxidative stress, and alterations in hormonal profiles [98]. PKCs and their isoforms have been linked to IPC pathways of protection.…”
Section: Age-related Differences Of Pkcs In Brainmentioning
confidence: 99%
“…These two phases of IT brought about by preconditioning possibly work by diverse mechanisms and in varied time frames in different tissues of the brain [12]. Factors that may affect the scope of CPC include age, gender, and strain of the animals used as models for cerebral ischemia [11,13].…”
Section: Understanding Cerebral Preconditioningmentioning
confidence: 99%